A Review on Sustainable Practices in Scientific Research (Global Journal of Science Frontier Research, 2024)
Many sustainable practices to reduce footprints in scientific research have been described. Plenty were proven to reduce environmental impacts while not affecting data quality. However, many scientists struggle with initiating change due to a lack in sustainability orientated education. A thorough understanding of sustainable practices is urgently needed to enable efficient and safe implementation. Therefore, the focus of this review is to provide a comprehensive collection and discussion of practices in chemical, biochemical, biologic and medical laboratories. Amongst others, strategies to reduce plastic waste, lessen energy consumption, reducing footprints when handling equipment and optimizing protocols or procurement will be included.